The Development of a Student Teachers Teaching Demonstration Performance Evaluation Tool - Enoc, Jeromil O. (European Scientific Journal, ESJ, 2019)
This paper focuses on developing a tool that measures the teaching demonstration performance of student teachers. To achieve this, constructs or factors that affect their teaching performance have to be determined first as these will be used as indicators in measuring the performance. Semi-structured interviews conducted among ten purposively selected student teachers and five cooperating teachers produced eighteen thematic statements as indicators in measuring teaching demonstration performance. These were added to fiftyfive indicators synthesized from the different literature reviews, producing a total of seventy-three indicators. After content and expert validation, these indicators were further deliberated and refined, producing only thirty-two which were used in a 5-point Likert scale questionnaire administered to twohundred and sixty-five cooperating teachers. Through principal component extraction, six constructs or factors with eigenvalues greater than one were extracted which were named as follows: classroom management, teaching strategy, lesson planning, professional behavior, accuracy and fluency of communication, and voice modulation. The variance explained by each of these factors became the basis in giving its weight in the proposed tool that would measure the teaching demonstration performance of student teachers.